El bullying y sus consecuencias en los estudiantes de 8vo y 9no año de educación general básica de la unidad educativa Lauro Damerval Ayora de la ciudad de Loja. Período académico 2014-2015 - Sarango Pardo, Yadira Viviana (2016)
This research work entitled: BULLYING AND ITS CONSEQUENCES IN THE 8th AND 9th YEAR OF GENERAL BASIC EDUCATION IN THE EDUCATIONAL UNIT OF LAURO DAMERVAL AYORA IN THE CITY OF LOJA. ACADEMIC PERIOD 2014-2015, had as general objective: Determine the status of bullying and its impact on students. This research is descriptive, the methods used were: scientific, descriptive, analytic-synthetic, inductive, deductive and statistical model. As a technique a survey of 724 students was applied, of which a sample corresponding to grades 8 and 9 representing 52 students was taken. By the implementation of these instruments, it was determined that within the Educational Unit, school harassment and/or bullying does exist. Thus concluding that within the modalities of bullying the more prevalent among students are: harassment, social manipulation, coercion and threat to integrity which have profound consequences on victims, as they become aggressive, strike, insult and withdraw. Therefore it is recommended that teachers be trained to treat bullying as a comprehensive problem that demands attention and resolutions at different socio-educational levels; performing preventive work with videos, handing out leaflets etc